EFEKTIVITAS METODE DISKUSI DENGAN MENGGUNAKAN MEDIA LEAFLET DAN MODUL TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP TOKOH MASYARAKAT TENTANG PENCEGAHAN MALARIA DI KECAMATAN KUTAMBARU KABUPATEN LANGKAT TAHUN 2015 - Rahayu Lubis; Emmy Yustina; Alam Bakti Keloko (Jurnal Ilmiah Keperawatan, 2018)
Malaria is an ancient disease, which is that still survive to this day, which is transmitted by the bite of Anopheles mosquito containing plasmodium, and poses a health problem that causes anemia, lowered work productivity and even death. Cases of clinical malaria in Langkat in the last three years has increased, which in 2010 from 47.18 per 1000 population increased to 63.79 per 1000 population in 2012. This type of research used in this study is quasi-experimental (quasi experimental) with a pretest-posttest design, which aim to analyze the effectiveness of the method of discussion by using the media module and leaflets to increase the knowledge and attitudes of community leaders on the prevention of malaria in Kutambaru Subdistrict, Langkat district. The population in this study are all Community Leaders in Kutambaru Subdistrict, Langkat district totaling 36 people. The sample is the entire population, numbering 36 people were divided into 2 groups: 18 people for the group threat with leaflet and 18 people for the group threat with modules. Analysis of the data using a statistical test Wilcoxon. The results of this study showed that the average improvement of knowledge and attitude was more effectively obtained through leaflet media compared to using modules media. It was found out that based on the knowledge of respondents, the difference in the mean value of leaflet media was 4.2 1and SD 1.49 and the mean values of modules media was 2,13 and SD 1.38. In terms of the average value of the difference based on the attitude of respondents for leaflet media was 6.34 , SD 1.49 , while for modules media was 3.32 and SD 1.42. Thew result of statistical test showed that the value p ( 0.000 ) < Î± ( 0,050 ). It is recommended that the health extension workers Puskesmas Maryke more active in providing health education to the community leaders on the prevention of malaria by using media modules and leaflets.